Ecological monitoring in the region of Akademik Vernadsky Antarctic station - Bondar, S. B.; Orlova, I. G.; Popov, Yu. I.; Ukrainsky, V. V.; Usenko, V. P. (Ukrainian Antarctic Journal, 2003)
The issues of organization and carrying out of ecological monitoring in the region of the Ukrainian Antarctic Station “Akademik Vernadsky” are taken up in the report. The information about the basic circulation flows, temporal (daily and annual) and spatial changeability of hydrological & hydrochemical ingredients as well as the vertical hydrological & hydrochemical water structure are presented on the basis of 1997-1998 experimental data. The description of the modern state of the chemical pollution of the basic elements of the Argentina Archipelago Islands` shallow water ecosystem. The broad spectrum of pollutants, such as different components of oil pollution, including carcinogenic polyaromatic hydrocarbons, highly toxic chlorinated hydrocarbons, heavy metals have been found in the majority of the ecosystem`s elements under analysis. The local areas of oil pollution have been found in the region of Galindez Isles. The obtained results are the part of the experimental data base for solving fundamental and applied problems including the problem of environmental protection. It is necessary to continue such investigations for studying the tendencies, for forecasting the vulnerable Antarctic ecosystems` state and for working up measures to protect ecosystems from the further pollution.